2020
DOI: 10.1038/s41467-020-14684-4
|View full text |Cite
|
Sign up to set email alerts
|

CASZ1 induces skeletal muscle and rhabdomyosarcoma differentiation through a feed-forward loop with MYOD and MYOG

Abstract: Embryonal rhabdomyosarcoma (ERMS) is a childhood cancer that expresses myogenic master regulatory factor MYOD but fails to differentiate. Here, we show that the zinc finger transcription factor CASZ1 up-regulates MYOD signature genes and induces skeletal muscle differentiation in normal myoblasts and ERMS. The oncogenic activation of the RAS-MEK pathway suppresses CASZ1 expression in ERMS. ChIP-seq, ATAC-seq and RNA-seq experiments reveal that CASZ1 directly up-regulates skeletal muscle genes and represses non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 54 publications
2
53
0
Order By: Relevance
“…By sequencing open chromatin, ATAC-seq can be used to study carcinogenesis. Transcription factors can affect the epigenetic modification of genes, thereby regulating gene expression, leading to the occurrence of cancer (13). People with specific gene mutations must avoid exposure to some environmental factors to reduce their risk of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By sequencing open chromatin, ATAC-seq can be used to study carcinogenesis. Transcription factors can affect the epigenetic modification of genes, thereby regulating gene expression, leading to the occurrence of cancer (13). People with specific gene mutations must avoid exposure to some environmental factors to reduce their risk of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al used ATAC-seq to reveal that CASZ1 regulates skeletal muscle genes by chromatin accessibility. The loss of CASZ1 activity impairs embryonal rhabdomyosarcoma differentiation and contributes to tumorigenesis (13). ATACseq analysis demonstrated that hypoxia treatment significantly reduced chromatin accessibility at RAR/RXR binding sites, while acetate supplementation restored chromatin accessibility and promoted tumor cell differentiation (14).…”
Section: Introductionmentioning
confidence: 99%
“…ATAC-seq was performed as previously described 69,70 . Approximately, 50,000 KCNR cells were pelleted and the Tn5 transposition reaction was performed with the Nextera kit (Illumina), according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Except that, p38 signaling pathway and wnt pathway were both proved to be responsible for the process [27,28]. As for the myogenic genes, MRFs, myoD, myoG, etc [29,30] were all reported as myogenic related genes.…”
Section: Discussionmentioning
confidence: 95%